The DREAM Dataset: Behavioural data from robot enhanced therapies for children with autism spectrum disorder - Billing, Erik (University of Skövde, 2020)
This dataset comprise behavioural data recorded from 61 children diagnosed with Autism Spectrum Disorders (ASD). The data was collected during a large-scale evaluation of Robot Enhanced Therapy (RET). The dataset covers over 3000 therapy sessions and more than 300 hours of therapy. Half of the children interacted with the social robot NAO supervised by a therapist. The other half, constituting a control group, interacted directly with a therapist. Both groups followed the Applied Behavior Analysis (ABA) protocol. Each session was recorded with three RGB cameras and two RGBD (Kinect) cameras, providing detailed information of children's behaviour during therapy. This public release of the dataset noes not include video recordings or other personal information. Instead, it comprises body motion, head position and orientation, and eye gaze variables, all specified as 3D data in a joint frame of reference. In addition, metadata including participant age, gender, and autism diagnosis (ADOS) variables are included.

All data in this dataset is stored in JavaScript Object Notation (JSON) and can be downloaded here as DREAMdataset.zip. A much smaller archive comprising example data recorded from a single session is provided in DREAMdata-example.zip. The JSON format is specified in detail by the JSON Schema (dream.1.1.json) provided with this dataset.

JSON data can be read using standard libraries in most programming languages. Basic instructions on how to load and plot the data using Python and Jupyter are available in DREAMdata-documentation.zip attached with this dataset. Please refer to https://github.com/dream2020/data for more details.

The DREAM Dataset can be visualized using the DREAM Data Visualizer, an open source software available at https://github.com/dream2020/DREAM-data-visualizer. The DREAM RET System that was used for collecting this dataset is available at https://github.com/dream2020/DREAM.

Denna databas omfattar beteendedata från 61 barn diagnostiserade med Autismspektrumtillstånd (AST). Insamlat data kommer från en storskalig studie på autismterapi med stöd av robotar. Databasen omfattar över 3000 sessioner från mer än 300 timmar terapi. Hälften av barnen interagerade med den sociala roboten NAO, övervakad av en terapeut. Den andra hälften, vilka utgjorde kontrollgrupp, interagerade direkt med en terapeut. Båda grupperna följde samma standardprotokoll för kognitiv beteendeterapi, Applied Behavior Analysis (ABA). Varje session spelades in med tre RGB-kameror och två RGBD kameror (Kinect) vilka analyserats med bildbehandlingstekniker för att identifiera barnets beteende under terapin. Den här publika versionen av databasen innehåller inget inspelat videomaterial eller andra personuppgifter, utan omfattar i stället anonymiserat data som beskriver barnets rörelser, huvudets position och orientering, samt ögonrörelser, alla angivna i ett gemensamt koordinatsystem. Vidare inkluderas metadata i form av barnets ålder, kön, och autismdiagnos (ADOS).

All data i den här databasen är lagrad som JavaScript Object Notation (JSON) kan här laddas ned i form av DREAMdataset.zip. Ett mycket mindre arkiv med exempeldata från en enstaka session kan laddas ned separat i form av DREAMdata-example.zip. JSON-formatet finns specificerat i form av ett JSON-schema som också bifogas med denna databas.

JSON kan läsas med hjälp av standardbibliotek i de flesta programspråk. Instruktioner för att läsa och visualisera datat med hjälp av Python och Jupyter bifogas i DREAMdata-documentation.zip. Vänligen besök https://github.com/dream2020/data för detaljer.

Databasen kan också visualiseras med hjälp av DREAM Data Visualizer, en enkel mjukvara som finns tillgänglig i form av öppen källkod via https://github.com/dream2020/DREAM-data-visualizer. Det fullständiga systemet som användes för inspelning av denna databas finns också tillgänglig via https://github.com/dream2020/DREAM.
The DREAM Dataset: Behavioural data from robot enhanced therapies for children with autism spectrum disorder
Keywords: Autistic Disorder; Autism; Behavior Therapy; Beteendeterapi; Robotics; Robotteknik; Computer graphics and computer vision; Datorgrafik och datorseende; Applied Psychology; Tillämpad psykologi